Optimalisasi Kebijakan Dalam Pengelolaan Kawasan Perbatasan Studi Kasus Kota Batam, Provinsi Kepulauan Riau - Rahayu, Sri; Junior, Johan Jeques (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2021)
Border areas in the Unitary State of the Republic of Indonesia are currently still in an alarming condition in various aspects of life, if there is no good and effective management by the Government, it will certainly threaten the sovereignty of the state. Seeing the various issues that have arisen related to the issue of population nationalism due to the lack of internet networks in accessing information, smuggling of goods, excavation of land resulting in the loss of islands located in border areas, etc. As a development priority in accordance with the President's Nawa Cita, it is necessary to strengthen the government regions in the management of development in the State Border Areas that are environmentally sound as the front porch of a highly competitive country, so that the Government of Indonesia applies a new paradigm in the management of the western border region with a combination of security and security approaches. welfare approach. The purpose of this study is to find out how the implementation of policies in border areas in responding to existing problems. This research uses qualitative method with descriptive research type. Secondary data sources are through national journal articles, using other sources such as social media such as (youtube, instagram, and twitter). The results of this study indicate that several existing policies can be re-optimized and able to solve problems in various sectors such as the threat of nationalism, coordination between institutions, involvement of the trade sector, and others